2013
DOI: 10.2174/1389200211314040012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteins Interaction with Curcumin Nanoparticles: Implications in Cancer Therapeutics

Abstract: Curcumin, a natural bioactive polyphenol, has been widely investigated as a conventional medicine for centuries. Over the past two decades, major pre-clinical and clinical trials have demonstrated its safe therapeutic profile but clinical translation has been hampered due to rapid degradation, poor water solubility, bioavailability and pharmaco-kinetics. To overcome such translational issues, many laboratories have focused on developing curcumin nanoformulations for cancer therapeutics. In this review, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…It is formerly considered as a drug possessing anti-angiogenic, anti-inflammation and antioxidation effect (Kwon et al, 2005;Suckow et al, 2006;EI-Azab et al, 2011;. Previous researches in 2013 have demonstrated the antitumor effect of Cum in a series of cancers (Bayet-Robert et al, 2013;Du et al, 2013;Kumaravel et al, 2013;Masuelli et al, 2013;Ono et al, 2013;Wei et al, 2013;Yallapu et al, 2013;Zhang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…It is formerly considered as a drug possessing anti-angiogenic, anti-inflammation and antioxidation effect (Kwon et al, 2005;Suckow et al, 2006;EI-Azab et al, 2011;. Previous researches in 2013 have demonstrated the antitumor effect of Cum in a series of cancers (Bayet-Robert et al, 2013;Du et al, 2013;Kumaravel et al, 2013;Masuelli et al, 2013;Ono et al, 2013;Wei et al, 2013;Yallapu et al, 2013;Zhang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…For most biomedical purposes, hard corona will likely improve the interaction between NPs and proteins, membranes, phospholipids, endocytic vesicles, organelles, and DNA (44)(45)(46).…”
Section: Importance Of Protein Corona For Biomedical Application Of Nmentioning
confidence: 99%
“…Recent studies have demonstrated the interaction of curcumin nanoparticles with plasma proteins, which is a new platform and can be used to improve cancer therapy [103].…”
Section: Curcumin Nanoparticles In the Treatment Of Cancermentioning
confidence: 99%